Estimated Carbon Absorption and Economic Benefits in Various Scenarios of Community Forest (HKm) Land Management Through The Scheme of Plan Vivo in The Upstream Watersheds (DAS) of Renggung River, Central Lombok Regency, Indonesia - L. Sukardi; Ismail Ismail; M. Husni Idris (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This study aims to (1) estimate carbon absorption and the economic benefits of HKM land management through Plan Vivo scheme and (2) determine the composition of plants to be prioritised. This research was conducted in the upstream watershed of Renggung River in Central Lombok. The calculation of the estimated carbon absorption was obtained using allometric equations, while the estimated economic benefits were calculated from the production of commodities that are grown and the potential of carbon trading. To determine the prioritised scenarios, Analitycal Hierarchy Process (AHP) was conducted. The time range of analysis is conducted within a period of 15 years with three scenarios of composition of plants : (1) scenario-1: 70% MPTs and 30% timber trees (2) scenario-2: 30% MPTs and 70% timber trees; and (3) scenario-3: 50% MPTs and 50% timber trees. The results of the study are as follows: (1) the increased absorption of carbon dioxide (CO2) for scenario-1 amounted to 87.54 tonnes/ha/yr, scenario-2 amounted to 138.93 tons/ha/yr, and scenario-3 for 113.88 ton/ha/yr; (2) The economic benefits for the scenario 1 is of IDR 37,882,304,- /hectare/year, the scenario-2 of IDR 22,875,951,- per hectare / year, and scenario-3 of IDR 31,685,853,- per hectare/year. Furthermore, based on the consideration of carbon absorption, economic benefits, and sociocultural aspects, the priorities to be developed is the scenario-2.